Optimasi Persediaan Bahan Baku Kain Produk Garmen dengan Metode Economic Order Quantity - Dyah Antika Septiana; Ralina Transistari; Jovita Angela (Cakrawangsa Bisnis: Jurnal Ilmiah Mahasiswa, 2022)
The Economic Order Quantity (EOQ) method has been well-known because of various research in operations management. However, in execution, this method is highly unique because it may consider several costs, including quantity discounts, to get optimal results. Furthermore, it is still quite rare for research related to inventory control in the garment manufacturing industry. This study aims to examine how the inventory control system for fabric raw materials uses the EOQ method, along with a comparative analysis of the cost of purchasing optimal fabric raw materials using quantity discounts. This quantitative descriptive nuance research took place at PT. Westa Pusaka Kusuma Yogyakarta (PT. WPK) as the object of research, by selecting four types of garment fabrics. The result is that the total inventory costs of the four types of fabrics much smaller than those that did not use EOQ optimization method.